1992
DOI: 10.1111/j.1365-2125.1992.tb05652.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine metabolism in neonates and infants.

Abstract: The metabolism of morphine was studied in seven fullterm neonates and five infants receiving a continuous infusion of morphine. All the patients had detectable plasma concentrations of morphine 3‐glucuronide (M3G) and 10 had detectable concentrations of morphine 6‐glucuronide (M6G). The mean plasma clearance of morphine was 20.1 ml min‐1 kg‐1 in neonates and 23.4 ml min‐1 kg‐1 in the group as a whole. The M3G/morphine ratio (7.3) was higher than that previously reported for preterm neonates (5.0) but lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 20 publications
1
25
2
1
Order By: Relevance
“…This ratio, however, is very low, even in the neonatal period, indicating that the contribution of sulfation to the metabolism of morphine is minimal. In another study, Choonara et al 9 demonstrated that full-term neonates and older infants have a well-developed mechanism for the glucuronidation of morphine at both position 3 and position 6. In all cases, the plasma concentrations of morphine-3-glucuronide were higher than those of morphine and the plasma concentrations of morphine-6-glucuronide were higher than those of morphine in 7 of the 10 infants in whom morphine-6-glucuronide was detectable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This ratio, however, is very low, even in the neonatal period, indicating that the contribution of sulfation to the metabolism of morphine is minimal. In another study, Choonara et al 9 demonstrated that full-term neonates and older infants have a well-developed mechanism for the glucuronidation of morphine at both position 3 and position 6. In all cases, the plasma concentrations of morphine-3-glucuronide were higher than those of morphine and the plasma concentrations of morphine-6-glucuronide were higher than those of morphine in 7 of the 10 infants in whom morphine-6-glucuronide was detectable.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, in premature infants who were given morphine intravenously, only morphine-3-glucuronide was detected in the plasma 2 hours after dosing, whereas morphine-6-glucuronide was detected in the plasma 24 hours after dosing. The plasma concentration ratios of morphine-3-glucuronide to morphine and morphine-6-glucuronide to morphine increased significantly with increasing birth weight 9. Morphine-6-glucuronide is a potent opioid agonist, whereas morphine-3-glucuronide functionally antagonizes several of the effects of both morphine and morphine-6-glucuronide 9.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evaluation of the predictive performance of the maturation model of Anand et al [8] Method I In order to evaluate the predictive performance of Equation 1, the clearance values of morphine for individual children (n = 147) were obtained from the literature [10][11][12][13][14][15][16][17][18][19]. The clearance data included pre-term (gestational age = 24-36 weeks, n = 75), term (gestational age = 37-41 weeks, n = 33), infants (1 week to 2 months, n = 12), younger children (>2 to 10 months, n = 15), and older children (3.1 to 5 years, n = 12).In these studies, clearance was estimated by non-compartmental as well was by compartmental analysis.…”
Section: Anand Et Al's Methodsmentioning
confidence: 99%